(untitled) (Research, Society and Development, 2021)
The new coronavirus disease (COVID-19) is characterized by a wide range of symptoms and clinical presentations. The most frequent symptoms are fever, headache, dry cough, anosmia, ageusia; it can also affect the gastrointestinal tract, the main symptoms being related to this system: diarrhea, abdominal pain, nausea and vomiting. Gastrointestinal symptoms are caused by an exacerbation of the immune system, not by direct injury of the virus to tissue. This is a descriptive, observational, retrospective study in the form of a case report that seeks to present an atypical manifestation of COVID-19 in a young female patient, resident of the city of Parnaíba-PI. The information and conduct adopted in the present case report were extracted from data from the patient’s medical record and from other documentation of complementary tests, both laboratory and imaging tests. Considering the large number of symptoms that are still unknown and that come from COVID-19, knowledge of the pathological bases of the disease is of great importance to be able to better conduct care and ensure faster treatment, especially in the face of more severe cases.